2009
DOI: 10.1002/asi.21095
|View full text |Cite
|
Sign up to set email alerts
|

Developing a visual taxonomy: Children's views on aesthetics

Abstract: This article explores the aesthetic design criteria that should be incorporated into the information visualization of a taxonomy intended for use by children. Seven elementary-school students were each asked to represent their ideas in drawings for visualizing a taxonomy. Their drawings were analyzed according to six criteria-balance, equilibrium, symmetry, unity, rhythm, and economy-identified as aesthetic measures in previous research. The drawings revealed the presence of all six measures, and three-unity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 58 publications
(59 reference statements)
1
10
0
Order By: Relevance
“…In the survey, the measure most prevalent among the four interfaces is unity. This emphasizes the point made by Large et al (2009) that unity is the principal aesthetic measure in interface design, visually combining all of the elements into one macro theme. This also confirms data from the interviews, as participants mentioned that they seek a visually pleasing interface that brings project information (such as projects, tasks, and resources) together in one place.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the survey, the measure most prevalent among the four interfaces is unity. This emphasizes the point made by Large et al (2009) that unity is the principal aesthetic measure in interface design, visually combining all of the elements into one macro theme. This also confirms data from the interviews, as participants mentioned that they seek a visually pleasing interface that brings project information (such as projects, tasks, and resources) together in one place.…”
Section: Resultsmentioning
confidence: 99%
“…Second, the subjects evaluated the presence of the five visual measures for all 12 screenshots. Options were limited to “Yes” or “No.” The visual analysis was based upon the research elaborated by Ngo et al (2003) and Large et al (2009).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ngo et al [81] identified measures for aesthetic design, including: balance, 'the distribution of optical weight'; equilibrium, 'a midway centre of suspension'; symmetry, the 'axial duplication'; sequence, "arrangement of objects in a layout in a way that facilitates the movement of the eye through the information displayed" (p. 30); unity, the 'totality of elements that is visually all one piece'; simplicity, 'directness'; economy, careful use of display elements; and rhythm, 'regular patterns of changes'. In one of the few studies on visualizations for children, Large et al [82] found that many of these criteria were present in children's drawings of an ideal interface, suggesting that perhaps young people gravitate naturally to the principles of aesthetical design.…”
Section: Engagementmentioning
confidence: 99%
“…Cone trees present an alternative for visualizing the taxonomy in three dimensions, as demonstrated by various applications such as Cat‐a‐Cone (Hearst and Karadi, 1997) and Lyberworld (Hemmje et al, 1994). The Cone also incorporates the findings of our previous research on the design of aesthetically pleasing interfaces for children, and includes balance, equilibrium, symmetry, unity, rhythm, and economy (Large et al, 2009b).…”
Section: Introductionmentioning
confidence: 99%